Rational design and synthesis of photo-responsive molecularly imprinted polymers for the enantioselective intake and release of l-phenylalanine benzyl ester on multiwalled carbon nanotubes. (31st May 2019) - Sajini, T.; Thomas, Renjith; Mathew, Beena
Abstract: A novel chiral sorbent forl -phenylalanine benzyl ester (L-PABE) is designed computationally by investigating the influence of the nature of template-monomer mole ratio and cross-linker. Density Functional calculations with B3LYP functional and generic 6-31G basis set was used as a computational tool with a photo-switchable azo-benzene derivative, 4-[(4-methacryloyloxy)phenylazo]benzoic acid (MPABA) as the functional monomer. 1:4 mol ratio of L-PABE and MPABA was chosen as the best imprinting ratio and N, N-ethylene bismethacrylamide (EBMAA) was used as the crosslinking agent. L-PABE imprinted polymer layered on multiwalled carbon nanotube (MWCNT) and conventional bulk MIP were also synthesized and characterized to investigate the influence of pre-organization of binding sites on the selectivity of L-PABE, respective non-imprinted polymers were also synthesized. MWCNT-MIPs and MIPs exhibit the largest adsorption capacity towards L-PABE. The synthesized polymers reveal characteristic adsorption features and selectivity towards L-PABE in comparison with its enantiomer analogues. Photo-regulated uptake and release studies of MWCNT-MIP and MIP on L-PABE were also done to determine the photo-switching reversibility of functional monomer. Graphical abstract: Image 1 Highlights: Rational design of chiral separation system using photo-responsive functional monomer. Photo-responsive polymers layered on MWCNTs were fabricated for the specific recognition of L-PABE molecule. Effect of cross-linker and mole ratio were determined computationally using DFT calculations with B3LYP functional and generic 6-31G basis set. Photo regulated uptake and release studies revealed the photo-responsive features of imprinted polymers.